Pragmatics Avoidance in Second Language Learning: Kurdish language as an Example - Faraj , Shakhawan Jalal Haji; Karim, Aso Abdulrahman (Zanco Journal of Human Sciences, 2021)
This paper is entitled Pragmatics Avoidance in Second Language Learning: Kurdish language as an example. This study is concerned with the Point that when a foreign language learner learns Kurdish Language, first s/he learns and controls the sematic aspect of the lexical items of the language. That is, in communication, they can use the vocabularies and sentences semantically. The research questions are: Do Second language learners, when learning pragmatics, have capacity to use linguistic elements? To what extent the pragmatics avoidance results in difficulty in Kurdish Language learning? In order to answer these tow questions, this study consists of two parts: theoretical and practical. It focuses on the importance of pragmatics of linguistic units (in addition to their semantic uses), and sheds light on the issues or difficulties that face Kurdish language learning regarding pragmatic competence.